2015
DOI: 10.3109/15622975.2015.1062551
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of local lithium concentrations in drinking water to regional suicide rates in Italy

Abstract: A proposed association between trace lithium concentrations in drinking water and risk of suicide was only partially supported, and mechanisms for potential clinical effects of trace levels of lithium are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…Where the mean level was comparable to levels found in previous studies [6,7,13,14,15,16,17,18], the range in the present study was generally more narrow. Previous studies that found a significant association with suicide consistently reported the highest lithium exposure levels with up to 59 µg/L in the Oita prefecture in Japan [16], 121 µg/L in Greece [13], and 219 µg/L in Texas [7].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Where the mean level was comparable to levels found in previous studies [6,7,13,14,15,16,17,18], the range in the present study was generally more narrow. Previous studies that found a significant association with suicide consistently reported the highest lithium exposure levels with up to 59 µg/L in the Oita prefecture in Japan [16], 121 µg/L in Greece [13], and 219 µg/L in Texas [7].…”
Section: Discussionsupporting
confidence: 87%
“…Potential confounders were selected based on the literature on central risk factors for suicide combined with a hypothesized association with lithium exposure, as well as findings from the reviewed literature on factors of influence on the association [6,7,13,14,15,16,17,18]. Covariates were included at an individual level and comprised gender and ethnicity (Danish origin, immigrant/descendant) as time constant confounders and age (10-year categories), employment (employed, unemployed, outside labor force) and civil status (cohabiting, living alone) as time-varying confounders.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thereafter, we showed an inverse association between lithium levels in drinking water and suicide rates for 18 municipalities of Oita prefecture in Japan in 2009 (Ohgami et al, 2009). However, this association was not found in a sample derived from 47 subdivisions in the East of England (Kabacs et al, 2011) and the association remains uncertain in a sample derived from 145 sites in Italy where lithium concentrations and local suicide rates were not significantly inversely related, except in 1980-1989, particularly among women, and also, based on weighted least-squared, bivariate regression modeling, lithium concentrations were significantly and negatively associated with overall suicide rates (in women and men), but only in 1980-1989(Pompili et al, 2015. A nationwide Austrian study found an inverse association between lithium levels in drinking water and suicide rates after adjustment of population density, per capita income, proportion of Roman Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/jad Catholics, as well as the availability of mental health service providers (Kapusta et al, 2011).…”
Section: Introductionmentioning
confidence: 85%